Managing the impact of volatility in international capital markets in an uncertain world - Jan Kregel (Levy Economics Institute of Bard College, 2009)
International financial flows are the propagation mechanism for transmitting financial instability across borders. They are also the source of unsustainable external debt. Managing volatility thus requires institutions that promote domestic financial stability, ensure that domestic instability is not transmitted internationally, and guarantee that international institutions and rules of the game are not themselves a cause of volatility. This paper analyzes proposals to increase stability in domestic markets, in international markets, and in the structure of the international financial system from the point of view of Hyman P. Minsky's financial instability hypothesis, and outlines how each of these three channels can produce financial fragility that lays the system open to financial instability and financial crisis.
Keywords: F33; F34; F55; G21; G28; 330; Minsky; financial crisis; international capital flows; risk reduction; hedging; speculation; international financial architecture; Bretton Woods system